If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -4x = 18 + -6x Solving 32 + -4x = 18 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 32 + -4x + 6x = 18 + -6x + 6x Combine like terms: -4x + 6x = 2x 32 + 2x = 18 + -6x + 6x Combine like terms: -6x + 6x = 0 32 + 2x = 18 + 0 32 + 2x = 18 Add '-32' to each side of the equation. 32 + -32 + 2x = 18 + -32 Combine like terms: 32 + -32 = 0 0 + 2x = 18 + -32 2x = 18 + -32 Combine like terms: 18 + -32 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| 10y^2+90y=0 | | H=15t-4.9t^2+3 | | -2(8x+3)=3x | | 4x-x=7squared | | 2n-8+6n=-14+8n | | 2z-15+3z=5-5z+10 | | 4(b-12)+1=17 | | 2x+32=60 | | 11+3x=15+9x-3x | | 2(m+1)+2=10 | | X-5x=6-2x+5 | | -24x+18=4 | | 3v+6=0 | | -7+x=7+9-5 | | -16=5v+11 | | 9x+6=3(x-4) | | -6+7k=1+7k | | 0.2x-1.6=2.4x+2.7 | | -8w+4=0 | | 2(r+7)=-4 | | 4m-3n=8form | | 7x+263.5=2717 | | 5b+3(b-4)=2(y+3) | | 3x+6(-2)=24 | | 0.6x+1.9=5 | | 5b+3(b-4)=2(y+2) | | -25x+1+10=10z+1 | | 5b+3(3-4)=2(y+2) | | 1.8c+32=39.2 | | 1.5x+3.4=7.9 | | y=2x+75 | | 5b+3(b-4y)=2(y+2) |